Intact sensory-motor network structure and function in far from onset premanifest Huntington’s disease - Gorges, Martin Peter; Mayer, Isabella Maria Sophie; Grupe, Gesa Sophie; Kammer, Thomas; Grön, Georg; Kassubek, Jan Rainer; Landwehrmeyer, Bernhard; Wolf, Robert Christian; Orth, Michael (Scientific reports, 2017)
Structural and functional changes attributable to the neurodegenerative process in Huntington’s disease (HD) may be evident in HTT CAG repeat expansion carriers before the clinical manifestations of HD. It remains unclear, though, how far from motor onset a consistent signature of the neurodegenerative process in HD can be detected. Twelve far from onset preHD and 22 age-matched healthy control participants underwent volumetric structural magnetic resonance imaging (MRI), diffusion tensor imaging (DTI), and resting-state functional MRI (11 preHD, 22 controls) as well as electrophysiological measurements (12 preHD, 13 controls). There were no significant differences in white matter macro- and microstructure between far from onset preHD participants and controls. Functional connectivity in a basal ganglia-thalamic and motor networks, all measures of the motor efferent and sensory afferent pathways as well as sensory-motor integration were also similar in far from onset preHD and controls. With the methods used in far from onset preHD sensory-motor neural macro- or micro-structure and brain function were similar to healthy controls. This suggests that any observable structural and functional change in preHD nearer to onset, or in manifest HD, at least using comparable techniques such as in this study, most likely reflects an ongoing neurodegenerative process.
Gesehen am 05.04.2018